Single‐shot imaging with higher‐dimensional encoding using magnetic field monitoring and concomitant field correction. Issue 3 (31st March 2014) - Testud, Frederik; Gallichan, Daniel; Layton, Kelvin J.; Barmet, Christoph; Welz, Anna M.; Dewdney, Andrew; Cocosco, Chris A.; Pruessmann, Klaas P.; Hennig, Jürgen; Zaitsev, Maxim
<x xml:space="preserve">Abstract</x> Purpose PatLoc (Parallel Imaging Technique using Localized Gradients) accelerates imaging and introduces a resolution variation across the field‐of‐view. Higher‐dimensional encoding employs more spatial encoding magnetic fields (SEMs) than the corresponding image dimensionality requires, e.g. by applying two quadratic and two linear spatial encoding magnetic fields to reconstruct a 2D image. Images acquired with higher‐dimensional single‐shot trajectories can exhibit strong artifacts and geometric distortions. In this work, the source of these artifacts is analyzed and a reliable correction strategy is derived. Methods A dynamic field camera was built for encoding field calibration. Concomitant fields of linear and nonlinear spatial encoding magnetic fields were analyzed. A combined basis consisting of spherical harmonics and concomitant terms was proposed and used for encoding field calibration and image reconstruction. Results A good agreement between the analytical solution for the concomitant fields and the magnetic field simulations of the custom‐built PatLoc SEM coil was observed. Substantial image quality improvements were obtained using a dynamic field camera for encoding field calibration combined with the proposed combined basis. Conclusion The importance of trajectory calibration for single‐shot higher‐dimensional encoding is demonstrated using the combined basis including spherical harmonics and concomitant terms, which treats the concomitant fields as an integral part of the encoding. Magn Reson Med 73:1340–1357, 2015. © 2014 Wiley Periodicals, Inc.